Should Echocardiographic Evaluation Be Performed Routinely in the First 72 Hours in Extremely Low Birth Weight Babies? - Ruya Colak; Senem Alkan Ozdemir; Ezgi Yangin Ergon; Ferit Kulali; Oguz Han Kalkanli; Tulin Gokmen Yildirim; Murat Muhtar Yilmazer; Cuneyt Zihni; Sebnem Calkavur (Gynecology Obstetrics & Reproductive Medicine)
Objective: Hemodynamically significant patent ductus arteriosus(hsPDA) is resulting in severe mortality and morbidity in infants with extremely low birth weight(ELBW). In our study, we aimed to evaluate the necessity of performing routine echocardiography(ECHO) in the first 72hours in ELBW infants.